2020
DOI: 10.1101/2020.07.21.214338
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The TAZ2 domain of CBP/p300 directs acetylation towards H3K27 within chromatin

Abstract: The closely related acetyltransferases CBP and p300 are key regulators of gene expression in metazoans. CBP/p300 acetylate several specific lysine residues within nucleosomes, including histone H3 lysine 27 (H3K27), a hallmark of active enhancers and promoters. However, it has remained largely unclear how specificity of CBP/p300 towards H3K27 is achieved. Here we show that the TAZ2 domain of CBP is required for efficient acetylation of H3K27, while curbing activity towards other lysine residues within nucleoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Recent data indicate that p300 directly engages nucleosome core particles (NCPs) through its ZZ (Zhang et al, 2018) and TAZ2 domains (Sheahan et al, 2020). Would then TAZ2-engagement also orient NCPs with respect to the HAT active site and specify nucleosome acetylation patterns?…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent data indicate that p300 directly engages nucleosome core particles (NCPs) through its ZZ (Zhang et al, 2018) and TAZ2 domains (Sheahan et al, 2020). Would then TAZ2-engagement also orient NCPs with respect to the HAT active site and specify nucleosome acetylation patterns?…”
Section: Resultsmentioning
confidence: 99%
“…Would then TAZ2engagement also orient NCPs with respect to the HAT active site and specify nucleosome acetylation patterns? In accordance with this possibility, it has been shown that the TAZ2 domain is required for efficient acetylation of H3K27, while curbing activity towards other lysine residues within nucleosomes (Sheahan et al, 2020). To test this model, we generated homogeneous 'structure-grade' NCPs as shown by single particle cryoEM (Fig.…”
Section: The Role Of the Taz2 Domain In P300 Regulation And Substrate...mentioning
confidence: 99%
See 2 more Smart Citations
“… 9 , 10 In addition, the interaction between the CBP transcriptional adaptor zinc-binding 2 (Taz2) domain and nucleosomal DNA, specifically acetylating histone H3 lysine 27 (H3K27), is essential for activating the enhancers and promoters of target genes. 11 Similarly, p53, classified as the pioneer transcription factor, can also directly bind with nucleosomal DNA via the interaction between the N-terminal region (amino acid 1–93) and the histone H3–H4. 12 Therefore, designing chemotherapy drugs targeting CBP/p300 cofactors or p53 is a potential strategy in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%